Resolving Requirement Ambiguities Using ‘Self-Organized Reuse’ Semantic Wiki and Multi Agent Technology (Journal of the College of Basic Education, 2022)
Requirement is the very starting point of software system where clients declare what they expect software system to provide. Crucial challenge facing software developer is to reveal valid specification from the requirement which most frequently holds ambiguity. The ambiguity is due to different understanding and mentality of both the customer and the developer.